2022
DOI: 10.1186/s13063-022-06259-z
|View full text |Cite
|
Sign up to set email alerts
|

INNODIA Master Protocol for the evaluation of investigational medicinal products in children, adolescents and adults with newly diagnosed type 1 diabetes

Abstract: Background The INNODIA consortium has established a pan-European infrastructure using validated centres to prospectively evaluate clinical data from individuals with newly diagnosed type 1 diabetes combined with centralised collection of clinical samples to determine rates of decline in beta-cell function and identify novel biomarkers, which could be used for future stratification of phase 2 clinical trials. Methods In this context, we have develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 18 publications
0
25
0
Order By: Relevance
“…T1DUK has as its principal aim "to help get immune therapy into the market as part of the management for type 1 diabetes" and has provided its infrastructure and expertise to various industry-and academia-led trials. T1DUK has also partnered with INNODIA on its master protocol platform (82). This standardization with platform protocols can clarify the regulatory pathway for DMTs for T1D and reduce logistical uncertainties in clinical development (83).…”
Section: Master Protocols and Platform Designsmentioning
confidence: 99%
“…T1DUK has as its principal aim "to help get immune therapy into the market as part of the management for type 1 diabetes" and has provided its infrastructure and expertise to various industry-and academia-led trials. T1DUK has also partnered with INNODIA on its master protocol platform (82). This standardization with platform protocols can clarify the regulatory pathway for DMTs for T1D and reduce logistical uncertainties in clinical development (83).…”
Section: Master Protocols and Platform Designsmentioning
confidence: 99%
“…Circulating microRNAs profiling from blood-derived plasma was performed in two independent cohorts (initial and validation cohort) of individuals enrolled within 6 weeks from clinical diagnosis of stage 3 T1DM in the European consortium INNODIA Natural history study (https://www.innodia.eu) 52 . The schematic of the study design is reported in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…In the current study we sought to characterise circulating miRNAs in a large cohort of T1DM individuals using a multiplatform sequencing approach coupled to the analysis of two cohorts of T1DM individuals belonging to the European INNODIA study consortium 52 . It is important to highlight that within the consortium, plasma samples were collected and processed uniformly and consistently, following a standardized operating procedure 51 adopted by multiple clinical centres and specifically designed to minimize pre-analytical biases that could potentially impact the stability and expression of circulating miRNAs 64 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a systems-based approach can address key questions with less bias and generate novel hypotheses on disease drivers. We used this strategy in the setting of a pan-European research consortium in which people with newly diagnosed type 1 diabetes as well as people at risk of developing type 1 diabetes (antibody positive) were enrolled into a master protocol 9 to conduct a prospective study in search of factors that correlate with the rate of decline in β-cell mass/function. This endeavor was supported by the Innovative Medicines Initiative-2 Joint Undertaking, where INNODIA was created, being a private-public partnership of 40 partners in 16 countries.…”
Section: Introductionmentioning
confidence: 99%